Representativeness heuristic is a potential danger to the diagnostic process (The Reasoner, 2025)
Similarly to the ordinary, the diagnostic process is characterized by the formulation of initial hypotheses to which probability judgments are associated, sometimes generated through heuristics and biases. The use of mental "shortcuts" can negatively affect the patient's management.
Keywords: Heuristics; Biases; Diagnosis; Representativeness